Artificial Leaf Leaf-inspired photosynthetic canopies for synthesis of energy and architectural space - Källmarker, Madeleine (My University, 2018)
In nature, there are countless design solutions which have been developed through evolution. Many of these solutions can be the answer to the challenge of sustainable living, thus nature has solved many of the challenges humans are facing today. With the challenge of climate change, there is a need to reduce and replace the use of fossil fuels with environmentally safe energy with the potential to supply the world’s high energy demand without being harmful to our planet. Fortunately, renewable energy sources existing on earth neither run out nor have any significant harmful effects on our environment. The sun has the potential to supply all the energy that humanity requires. Solar cells, where solar energy is converted directly into electricity, has been improved over the last decades. However, the issue with solar panels is that the electricity is not produced when and where it is needed the most. Thus, a way to efficiently store the energy is needed. By converting solar energy into storable chemical energy, the intermittency problem with solar energy can be solved. Hydrogen gas with its great characteristics of storing energy could be the answer to this problem. With inspiration from the leaf of a tree, the aim of this project is to design energy generating canopies by mimicking the leaf’s photosynthesis as well as utilizing the structural characteristics of the leaf. Furthermore, the project aims to inspire cross research as well as innovative sustainable solutions. As a result of the project, a physical built prototype has been constructed where hydrogen gas is generated from water through electrolysis. The design of the canopy is based on the characteristics of the present elements water and hydrogen gas. The prototype is a 1:1 scale canopy of 4 x 3 meters where hydrogen gas is generated by solar energy. The hydrogen gas is then stored in an inflatable structure until it is needed for usage. The project is a result of interdisciplinary research between the department of Physics and the department of Architecture and Civil Engineering of Chalmers. Through inspiration from nature, this thesis shows how the challenge of sustainability can be solved with new technology within the field of renewable energy sources. With research and new technology of today, we can solve the challenge of today; to make the world independent of fossil fuels. This project is one example of biomimicry, there are countless solutions in nature waiting to be explored by human research.
Keywords: Fysik; Physical Sciences